Scale and scope of university technology transfer: A flexible multiproduct approach - Jose Polo; Néstor Duch; Martí Parellada (European Regional Science Association (ERSA), 2010)
This paper empirically analyzes the economies of scale and economies of scope in the production of research and technology transfer outputs in the Spanish public university system. We employ the flexible fixed quadratic cost (FFQC) function which relates the total university R&D expenditure with different outputs of research and technology transfer, from where we compute the ray economies of scale, the specific economies of scale and the economies of scope. From a survey of Technology Transfer Offices (TTO) network in Spain, data from the Institute of Documentary Studies on Science and Technology (IDSST) and from the Rector's Conference of Spanish Universities, we constructed a dataset for the period 2004 - 2008 and for 45 public universities. The results support the presence of ray economies of scale and product specific economies of scale. Our results also show that the cost subadditivity is positive constraint, meaning that there are economies of scope.
Keywords: 330